The co-evolution of seaports and dry ports in Shandong province in China under the Belt and Road Initiative - Yiran Sun; Yuqian Wang; Jingci Xie (Journal of Shipping and Trade (JST), 2022)
Nowadays, Belt and Road Initiative (BRI) has been prosperous for a long time and brings plenty of opportunities to every aspect of China. As a coastal province with lots of port resources, Shandong province has implemented port integration, and there are some operation problems arising, too. In order to make the seaports and dry port reach their full potential, it is very crucial to explore the evolution trend of the ports, which can offer more chances for future development. Based on related theory, this article analyses the evolution of seaports and dry ports in Shandong Province, combined with the background of BRI. After showing the trend of port evolution, this paper points out the co-evolution mechanism of seaports and dry ports and describe a dry port-seaport logistics network in Shandong Province, which results from the mutual influence of seaports and dry ports. Finally, considering the influence of the BRI, this article points out that Shandong Province should take the inland cities as the basis and consider the various costs of the ports to fully take part in the Belt and Road Initiative, when constructing a logistics network.
Keywords: 650; Belt and Road Initiative; Dry port-seaport; Network evolution